Co-receptor mediated regulation of T cell receptor signalling in natural killer cells - Karahan, Zeynep Sena. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2022)
Antigen-specific cancer immunotherapy has been developing since the 1990s and showing promising results. T cell receptors (TCR) and Chimeric antigen receptors (CAR) are the most commonly used tools for modifying T cells with antigen-specific cytotoxicity. TCR-T cells have the mispairing problem caused by the endogenously produced TCR chains pairing with the ectopically delivered ones and creating T cells with unknown specificity. While NK cells contain all the necessary molecules for the downstream signalling pathway of TCR-CD3 mediated cytotoxicity they do not have the full TCR-CD3 complex. In order to overcome the mispairing problem in T cells, TCR and CD3 genes are used to modify NK cells instead of T cells. TCR-NK cells have shown promising cytotoxic effects against their target cells in vitro and in vivo, however their signalling mechanisms remain to be studied. CD8 coreceptors are known to increase the strength of the bond between TCR-CD3 and peptide-major histocom patibility complex (pMHC) and also aid the signalling cascade to begin. There are two types of CD8 chains, α and β. While T cells mostly utilise CD8αβ heterodimers, some cells have the CD8αα homodimer. This thesis aims to investigate the possible role of CD8 dimers in TCR-NK cells in order to optimise the TCR-NK cell cytotox icity. Lentiviral constructs containing CD8 genes were delivered to TCR-NK cells. These TCR-NK-CD8 cells’ cytotoxicity and antigen-specificity against the target cells were analysed with degranulation, cytokine secretion and real-time cell analysis assays. Western blot analysis was performed to observe the upregulated signalling pathways if present. Our results provide valuable data on the effect of CD8 coreceptors on TCR- NK cells.
Keywords: Cancer -- Immunotherapy.; T cells -- Receptor.